Microbial prodigiosin shows broad-spectrum bioactivity confirmed by experimental and computational analyses - Rafiq, Muhammad; Huda, Noor ul; Hassan, Noor; Ali, Hazrat; Tawab, Abdul; Bashir, Rizwan; Iqbal, Naveed; Rafaque, Zara; Ahmad, Faisal; Wang, Yanyan; Rauf, Waqar; Saqib, Anam; et al. (Frontiers in Microbiology, 2025)
The growing demand for natural bioactive compounds highlights the need for antimicrobial and antioxidative metabolites derived from microbial sources. Among them, prodigiosin, a red pigment from Serratia marcescens, displays potent antioxidant and antimicrobial properties. However, optimizing its production and understanding molecular interactions remain challenging. In this study, we identified an optimized process for enhanced yield using peptone meat extract (PM) media at an incubation temperature of 30 °C, which notably outperformed other tested conditions and media. The purified red pigment was further characterized by column and thin-layer chromatography, UV–visible spectrophotometry, Fourier Transform Infrared (FT-IR) spectroscopy, and Mass Spectrometry (ESI-MS/MS). The pigment demonstrated an Rf value of 0.93 through column chromatography and TLC. The structural characteristics were established using UV–Vis (λmax 536 nm), FT-IR, and ESI-MS/MS (m/z 324.3 amu), consistent with the prodiginine family. The characterized and purified prodigiosin showed excellent antibacterial activity against Gram-negative bacteria Escherichia coli (28.2 ± 0.57 mm) and Gram-positive bacteria Bacillus subtilis (23.58 ± 0.6 mm), together with antifungal activity against Fusarium oxysporum and Aspergillus niger. Antioxidant analysis showed a dose-dependent radical-scavenging activity of up to 37.5% at 1000 μg/mL. To understand the mechanistic pathways, molecular docking revealed high binding affinities of the produced metabolite with key target sites as FKS1 (−7.2 kcal/mol) for antifungal inhibition, FabH (−7.3 kcal/mol) against antibacterial inhibition, and Keap1 (−8.3 kcal/mol) for antioxidant activity. Our findings not only feature prodigiosin’s broad-spectrum bioactivity but also offer its interaction with molecular targets, providing the basis for developing this metabolite as a natural therapeutic agent in multiple industrial applications, including pharmaceuticals and agriculture.